The Effect of Drill Controled One Arm And Drill Catch Up Freestyle Swimming Training on Men Swimming Athletes - Rusdi, Rusdi; Lauh, Whalsen Duli Agus; Risa, Risa (Universitas PGRI Palembang, 2024)
This study aims to determine the differences in the effect of Drill Controlled One Arm and Drill Catch Up Exercises on Swimming Speed ​​for Freestyle in Men's Swimming Athletes at Pontianak Swimming Club. The method used in this research is the experimental method. The sample used in this study were 16 athletes from swimming clubs. Based on the results of the research, the Drill Controled One Arm and Drill Controled One Arm exercises both have an influence on speed in the free swimming style of men's swimming athletes at the Pontianak Swimming Club. Based on the results of the study showed that the results of the Drill Catch Up exercise were better than the Controlled One Arm Exercise for freestyle swimming in male swimming athletes at the Pontianak Swimming Club